THE EFFECT OF ANAGRAM GAME ON THE EIGHTH GRADE STUDENTS’ VOCABULARY MASTERY AT SMPN 3 BALARAJA - Dewi Kartikasari; Arjulayana - Arjulayana; Aidil Syah Putra (Universitas Muhammadiyah Tangerang, 2021)
This research was aimed to know the effect of Anagram Game on students’ vocabulary mastery. This research used quantitative method, with quasi-experimental design. This research was conducted in SMPN 3 Balaraja. The number of the sample of the research was 70 students of eighth grade. The instrument in this research was divided into two steps of test, namely pre-test and post-test. Based on the criteria of hypothesis test that if tcount < ttable then Ho is accepted, it means that there is no significant difference students’ result of learning vocabulary mastery between students in experiment class who were taught by using Anagram Game and the students in control class who were not taught by using Anagram Game. Otherwise, if tcount > ttable then H1 is accepted, it means there is any significant difference of students’ result of learning vocabulary mastery between students in experiment class who were taught by using Anagram Game and students in control who were taught by using Anagram Game. The result of the calculation was t – count of ɑ = 5% was 2.04, and for t – table was 1.99. It proved that Anagram Game gave effect on students’ vocabulary mastery.